A Trend Analysis Of Patient Visits Following The Implementation Of Digital Marketing Strategies At Fauziah Mother And Child Hospital, Tulungagung - Agus Baijuri; Pipit Festi; Ariesta Wira Permana (LP2IHKI UMSurabaya, 2026)
Abstract Background : The advancement of information technology has encouraged hospitals to utilize digital marketing strategies as a means of promoting healthcare services. Digital marketing is considered effective in improving information dissemination, increasing public awareness, and enhancing patient visit rates. Aims : This study aimed to determine the trends in patient visits following the implementation of digital marketing strategies at Fauziah Mother and Child Hospital, Tulungagung. Methods : : This study employed a quantitative descriptive method with a retrospective approach. Data were obtained from outpatient and inpatient patient visit reports at Fauziah Mother and Child Hospital, Tulungagung, from January to December 2025. Data analysis was conducted using frequency distribution, percentage analysis, and patient visit trend analysis.. Results : The highest number of outpatient visits was recorded in the Pediatric Clinic with 13,607 patients, while the Obstetrics and Gynecology (Ob-Gyn) Clinic accounted for 1,457 patients. In inpatient services, the number of pediatric patients reached 1,285, while maternal patients totaled 455. An increasing trend in patient visits was observed from August to December 2025. Conclusion : The digital marketing strategies implemented by Fauziah Mother and Child Hospital, Tulungagung, contributed to increasing the exposure of healthcare services to the community, which subsequently impacted the growth of patient visits, particularly in pediatric outpatient and pediatric inpatient services. The optimal utilization of digital media can serve as an effective marketing strategy to enhance hospital competitiveness in the digital era. Keywords : Patient Visit Trends, Digital Marketing, Hospitals, Healthcare Marketing, Outpatient Services. Abstrak Latar Belakang : Perkembangan teknologi informasi mendorong rumah sakit untuk memanfaatkan strategi digital marketing sebagai sarana promosi layanan kesehatan. Digital marketing dinilai efektif dalam meningkatkan penyebaran informasi, awareness masyarakat, dan jumlah kunjungan pasien. Tujuan : Mengetahui Tren Kunjungan Pasien Setelah Implementasi Pemasaran Digital di RSIA Fauziah Tulangan. Metode : Penelitian ini menggunakan metode deskriptif kuantitatif dengan pendekatan retrospektif. Data diperoleh dari laporan kunjungan pasien rawat jalan dan rawat inap RSIA Fauziah Tulungagung periode Januari–Desember 2025. Analisis data dilakukan menggunakan distribusi frekuensi, persentase, dan analisis tren kunjungan pasien. Hasil : Jumlah kunjungan rawat jalan tertinggi terdapat pada Poli Anak sebanyak 13.607 pasien, sedangkan Poli Obgyn sebanyak 1.457 pasien. Pada layanan rawat inap, jumlah pasien anak mencapai 1.285 pasien dan pasien ibu sebanyak 455 pasien. Tren peningkatan kunjungan pasien terjadi pada periode Agustus hingga Desember 2025. Kesimpulan : Strategi digital marketing yang dilakukan RSIA Fauziah Tulungagung berkontribusi dalam meningkatkan eksposur layanan kesehatan kepada masyarakat sehingga berdampak pada peningkatan kunjungan pasien, terutama pada layanan Poli Anak dan rawat inap anak. Pemanfaatan media digital yang optimal dapat menjadi strategi pemasaran efektif dalam meningkatkan daya saing rumah sakit di era digital. Kata Kunci : Tren Kunjungan Pasien, Pemasaran Digital, Rumah Sakit, Pemasaran Kesehatan, Rawat Jalan